APLIKASI AKAD-AKAD MUAMALAH PADA BANK SYARIAH - Rahmi, Rahmi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
The Islamic / Syaria Bank is a financial institution that is engaged in activities for the purpose of getting financial benefit (profit oriented). In Islam looking for profit is allowed as long as the profit obtained is not contrast to Islamic teachings. Islamic banks which are based on Islamic teachings definately attempt to get benefits that are not againts its principles. In order to obtain the benefits through the right way, Islamic bank implements muamalah contract which is profitoriented, that is selling (tijarah) contract such as albai’u contract (purchase), syirkah (investment) , and Ijarah (rent). Beside that, the bank remains implementing nonbusiness oriented contract (nonprofit oriented), as wakalah (representation), rahn (mortgage), and kafalah (insurance).